Composite hydrogel

By preparing tannin-nano silver complex and combining nanocellulose, a composite hydrogel with long-term adhesion, antibacterial and antioxidant was prepared, which solved the mechanical properties and cellular phases of existing hydrogels in the field of biomedical science. The problem of insufficient capacity has achieved efficient adhesion and antibacterial effects.

CN119490718AInactive Publication Date: 2025-02-21QILU UNIVERSITY OF TECHNOLOGY (SHANDONG ACADEMY OF SCIENCES)
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411834275.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-13
Publication Date
2025-02-21
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

In the field of biomedical science, the existing composite hydrogels are limited in their application due to poor mechanical properties, cell compatibility or insufficient tissue adhesion, and especially the adhesion properties are difficult to maintain for a long time.

Method used

By preparing tannin-nano silver composites and using them to stimulate radical polymerization of acrylic monomers, combining nanocellulose with nanocellulose to improve strength, a nanocellulose-polyacrylic-tannin-nano silver composite hydrogel was obtained. The hydrogel generates free electrons through the plasma resonance of silver nanoparticles, promotes the reversible redox reaction of quinone-phenol, stimulates the free radical initiator, and causes the acrylic monomer to rapidly polymerize at room temperature.

Benefits of technology

The composite hydrogel has long-term adhesion, antibacterial and antioxidant ability, and can maintain adhesion performance for more than 30 days. It has high protein adsorption and strong antioxidant ability, which can effectively inhibit free radicals and bacteria.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119490718A_ABST
    Figure CN119490718A_ABST
Patent Text Reader

Abstract

The invention relates to composite hydrogel, and belongs to the field of new materials. The preparation method of the composite hydrogel comprises the following steps: S1, preparing a tannin-nano-silver compound; s2, utilizing the tannin-nano-silver compound to excite free radical polymerization of an acrylic monomer, and utilizing nano-cellulose to improve the strength, so as to obtain the nano-cellulose-polyacrylic acid-tannin-nano-silver hydrogel. Compared with the prior art, the composite hydrogel disclosed by the invention is high in strength, shows long-term adhesion performance and antibacterial and antioxidant performance, and has a potential application prospect in the field of biological medicines.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention discloses a composite hydrogel and belongs to the field of new materials. Background Art

[0002] Hydrogels have attracted widespread attention as ideal materials for repairing soft tissues including skin, cartilage and muscle. However, the poor mechanical properties of hydrogels limit their application in the biomedical field. Various methods have been used to prepare hydrogels with excellent mechanical properties, such as composite nanohydrogels, topological hydrogels, double network hydrogels, semi-interpenetrating network hydrogels, etc. However, many composite hydrogels with good mechanical properties have poor cell compatibility or tissue adhesion, which seriously limits the contact between hydrogels and human tissues.

[0003] The adhesion of wound dressings can effectively reduce the loss of tissue fluid and reduce wound infection. Inspired by mussel protein, scientists have prepared a variety of adhesive hydrogels. Gan et al. used methacrylamide dopamine to simulate mussels to prepare hydrogels. Its catechol structure can form physical or chemical bonds with different surfaces, improve the affinity with cells / tissues, and make the gel have good biocompatibility and cell / tissue adhesion. However, the extraction of dopamine is extremely complicated and the yield is low. In addition, the adhesion properties of pure dopamine functionalized hydrogels cannot usually be maintained for a long time. This is because some catechol groups in the adhesive hydrogel are converted into quinone groups through oxidation, resulting in the loss of adhesion of the hydrogel. Summary of the invention

[0004] The present invention aims at solving the above-mentioned deficiencies of the prior art and provides a composite hydrogel with long-term adhesion, antibacterial and antioxidant properties.

[0005] The technical task of the present invention is achieved in the following manner: the composite hydrogel, the preparation method of which comprises:

[0006] S1. Preparation of tannin-nanosilver composite;

[0007] S2. Use tannin-nanosilver complex to stimulate free radical polymerization of acrylic acid monomers, and use nanocellulose to improve the strength to obtain nanocellulose-polyacrylic acid-tannin-nanosilver hydrogel.

[0008] Preferably, the tannin-nanosilver composite in step S1 is prepared by the following method:

[0009] The tannin and silver nitrate are mixed and reacted under light-proof conditions to obtain a tannin-nanosilver complex.

[0010] Preferably, the mass ratio of tannin to silver nitrate is 1:(0.1-2), particularly preferably 1:(0.4-1.5).

[0011] Preferably, the reaction time of tannin and silver nitrate is 0.5-5 hours, particularly preferably 0.5-3 hours.

[0012] Preferably, the reaction pH of tannin and silver nitrate is 5-7, particularly preferably 6-7. The pH value of the reaction system can be adjusted using K2CO3, NaOH or KOH.

[0013] Preferably, the tannin-nanosilver complex obtained in step S1 is spherical particles with a particle size of 10-30 nm.

[0014] Preferably, the tannin is larch tannin, bayberry tannin, quebracho tannin and / or black wattle tannin.

[0015] Preferably, the hydrogel in step S2 is prepared by the following method:

[0016] The tannin-nanosilver composite, nanocellulose, acrylic acid monomer and crosslinking agent are uniformly mixed, and then an initiator is added, and after being uniformly stirred, the mixture is reacted at a temperature not higher than 30° C. for 20-30 minutes to obtain a nanocellulose-polyacrylic acid-tannin-nanosilver composite hydrogel.

[0017] Preferably, after the materials in step S2 are mixed, they are stirred for 3-5 minutes, poured into a film-forming container, and reacted at 15-30° C. for 20-30 minutes to obtain a nanocellulose-polyacrylic acid-tannin-nanosilver composite hydrogel.

[0018] Preferably, the volume ratio of nanocellulose to tannin-nanosilver composite is (1-5):1, particularly preferably (1-3):1.

[0019] Preferably, the mass ratio of nanocellulose to acrylic acid is 1:(1-30), particularly preferably 1:(10-20).

[0020] Preferably, the amount of the initiator is 0.05-2% of the mass of the acrylic acid monomer, particularly preferably 0.5-1.5%, and the initiator is potassium persulfate or ammonium persulfate.

[0021] Preferably, the amount of the crosslinking agent is 0.5-3% of the mass of the acrylic acid monomer, particularly preferably 2-3%, and the crosslinking agent is polyethylene glycol diacrylate or N,N'-methylenebisacrylamide.

[0022] Preferably, the nanocellulose is nanocrystalline cellulose.

[0023] Compared with the prior art, the composite hydrogel of the present invention has the following outstanding beneficial effects:

[0024] 1. The silver nanoparticle surface plasma resonance generates free electrons, and a dynamic quinone-phenol reversible redox reaction occurs. The tannin-nanosilver redox system can excite the free radical initiator, causing the acrylic acid monomer to polymerize rapidly within 20-30 minutes at room temperature. Conventional acrylic acid free radical polymerization requires a reaction temperature of 60-90°C for 6-12 hours;

[0025] Second, the surface plasmon resonance of silver nanoparticles generates free electrons, and a dynamic quinone-phenol reversible redox reaction occurs, which gives the hydrogel material long-term adhesion properties, and its adhesion properties can be maintained for more than 30 days;

[0026] 3. The addition of tannin gives the composite hydrogel a protein adsorption capacity of up to 10.04g / g; good UV shielding and antioxidant capabilities, and the DPPH free radical inhibition rate can reach more than 90%; excellent antibacterial ability, with the inhibition zone for Escherichia coli and Staphylococcus aureus reaching more than 30mm;

[0027] 4. The addition of nanocellulose and tannin improves the biocompatibility of the composite hydrogel and has good development prospects in the field of biomedicine. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Attached Figure 1 It is a reaction route diagram of the composite hydrogel preparation method of the present invention;

[0029] Attached Figure 2 is a graph of the morphology and particle size of the tannin-nanosilver composite of the embodiment;

[0030] Attached Figure 3 is a graph of DPPH free radical scavenging rate of composite hydrogel of the embodiment;

[0031] Attached Figure 4 is the stress-strain curve of the composite hydrogel of the embodiment;

[0032] Attached Figure 5 is a graph of the bovine serum albumin (BSA) adsorption amount of the composite hydrogel in the embodiment;

[0033] Attached Figure 6 It is the inhibition zone of the composite hydrogel of the example against Escherichia coli and Staphylococcus aureus. DETAILED DESCRIPTION

[0034] The present invention will be further described below in conjunction with the accompanying drawings and specific embodiments, but they are not intended to limit the present invention.

[0035] The materials involved in all embodiments of the present invention can be obtained from commercial channels.

[0036] Unless otherwise specified, "%" in the examples refers to mass percentage.

[0037] As attached Figure 1 As shown, the preparation process of the composite hydrogel of the present invention is to first prepare a tannin-nanosilver composite, and then use it to excite a free radical initiator, such as ammonium persulfate, potassium persulfate, etc., so as to accelerate the free radical polymerization of acrylic acid monomers, so that it can be polymerized in a short time, and nanocellulose is added to improve the strength to obtain a nanocellulose-polyacrylic acid-tannin-nanosilver hydrogel.

[0038] Example 1

[0039] (1) Prepare a solution of 8.5 mg / L black wattle tannin, adjust its pH to 7 with 1 wt.% K2CO3, add 0.1 mol / L AgNO3 solution at a ratio of tannin:AgNO3 absolute dry mass = 1:1, and react for 1 h in the dark to obtain silver nanoparticles with a particle size of 17-28 nm (see attached Figure 2 c, f).

[0040] (2) Take 20 ml of nanocrystalline cellulose with a concentration of 0.87% and add it to a beaker, then add 10 ml of the prepared tannin-nanosilver complex and stir evenly. Add 0.025 g of ammonium persulfate (APS), 5 ml of deionized water, 2.8 g of acrylic acid monomer, and 0.07 g of polyethylene glycol diacrylate (PEGDA), place it on a magnetic stirrer, mix it at 25°C for 3 minutes, pour it into a plastic culture dish after mixing evenly, and let it stand for 20 minutes to form a nanocellulose-polyacrylic acid-tannin-nanosilver composite hydrogel.

[0041] Example 1 The composite hydrogel obtained has a tensile strength of 0.15 MPa and an elongation at break of 212% (e.g. Figure 4 The absorption rate of bovine serum albumin (BSA) was 10.4 g / g gel (as shown in CNC2-PAA-T-Ag1 sample in b). Figure 5 b) CNC2-PAA-T-Ag1 sample). DPPH free radical scavenging rate was 90.6% (as shown in the attached Figure 3 b) the cell activity was 95.5% after 24 hours (MTT method). It has a significant inhibitory effect on Escherichia coli and Staphylococcus aureus (as shown in Figure 6 a, b shows the CNC2-PAA-T-Ag1 sample).

[0042] The bovine serum albumin (BSA) absorbance test method is as follows:

[0043] The composite hydrogel was cut into two sample blocks of 40 × 40 mm, named sample a and sample b, with the mass m a1 ,m b1Prepare a 5wt.% bovine serum albumin solution, immerse sample a in 20ml BSA solution, and sample b in 20ml deionized water as a control. Incubate at 38℃ for 24h, remove the sample, drain the surface liquid, and weigh its mass m a2 ,m b2 The bovine serum albumin adsorption capacity (mg protein / g hydrogel) of the composite hydrogel was designed according to Formula I.

[0044]

[0045] Embodiment 2:

[0046] (1) A black wattle tannin solution with a concentration of 8.5 mg / L was prepared, and its pH was adjusted to 7 with 1 wt.% K2CO3; 0.1 mol / L AgNO3 solution was added at a ratio of tannin:AgNO3 absolute dry mass ratio of 1:0.6, and the reaction was carried out in the dark for 1 h to prepare silver nanoparticles with a particle size of 15-28 nm (such as Figure 2 b, e).

[0047] (2) Take 20 ml of nanocrystalline cellulose with a concentration of 0.87% and add it to a beaker, then add 10 ml of the prepared tannin-nanosilver complex and stir evenly. Add 0.025 g of ammonium persulfate (APS), 5 ml of deionized water, 2.8 g of acrylic acid monomer, and 0.07 g of polyethylene glycol diacrylate (PEGDA), place it on a magnetic stirrer, mix it at 25°C for 3 minutes, pour it into a plastic culture dish after mixing evenly, and let it stand for 20 minutes to form a nanocellulose-polyacrylic acid-tannin-nanosilver composite hydrogel.

[0048] Example 2 The composite hydrogel obtained has a tensile strength of 0.20 MPa and an elongation at break of 292% (e.g. Figure 4 The bovine serum albumin (BSA) absorption rate is 10.0 g / g gel (as shown in CNC2-PAA-T-Ag0.6 sample in b). Figure 5 b shows the CNC2-PAA-T-Ag0.6 sample, and the test method is the same as in Example 1). The DPPH free radical scavenging rate is 89.2% (as shown in Figure 3 b) the cell activity was 90.1% after 24 hours (MTT method). It has a significant inhibitory effect on Escherichia coli and Staphylococcus aureus (as shown in Figure 6 a, b shows the CNC2-PAA-T-Ag0.6 sample).

[0049] Embodiment 3:

[0050] (1) A black wattle tannin solution with a concentration of 8.5 mg / L was prepared, and its pH was adjusted to 7 with 1 wt.% K2CO3; 0.1 mol / L AgNO3 solution was added at a ratio of tannin: AgNO3 absolute dry mass ratio = 1:0.4, and the reaction was carried out in the dark for 1 h to prepare silver nanoparticles with a particle size of 11-26 nm (such as Figure 2 a, d).

[0051] (2) Take 20 ml of nanocrystalline cellulose with a concentration of 0.87% and add it to a beaker, then add 10 ml of the prepared tannin-nanosilver complex and stir evenly. Add 0.025 g of ammonium persulfate (APS), 5 ml of deionized water, 2.8 g of acrylic acid monomer, and 0.07 g of polyethylene glycol diacrylate (PEGDA), place it on a magnetic stirrer, mix it at 25°C for 3 minutes, pour it into a plastic culture dish after mixing evenly, and let it stand for 20 minutes to form a nanocellulose-polyacrylic acid-tannin-nanosilver composite hydrogel.

[0052] The tensile strength of the composite hydrogel obtained in Example 3 was 0.11 MPa and the elongation at break was 133%. Figure 4 The bovine serum albumin (BSA) absorption rate was 11.2 g / g gel (as shown in CNC2-PAA-T-Ag0.4 sample in b). Figure 5 b shows the CNC2-PAA-T-Ag0.4 sample, and the test method is the same as in Example 1). The DPPH free radical scavenging rate is 93.5% (as shown in Figure 3 b) the cell activity was 90.5% after 24 hours (MTT method). It has a significant inhibitory effect on Escherichia coli and Staphylococcus aureus (as shown in Figure 6 a, b shows the CNC2-PAA-T-Ag0.4 sample).

[0053] Embodiment 4:

[0054] As described in Example 2, except that the amount of nanocrystalline cellulose used in step (2) is 10 ml.

[0055] Example 4 The tensile strength of the composite hydrogel obtained was 0.16 MPa and the elongation at break was 148% (as Figure 4 The bovine serum albumin (BSA) absorption rate was 9.0 g / g gel (as shown in a). Figure 5 The DPPH free radical scavenging rate was 94.0% (as shown in the CNC1-PAA-T-Ag0.6 sample in a, and the test method was the same as in Example 1). Figure 3a), the cell activity was 91.5% after 24 hours (MTT method). It has a significant inhibitory effect on Escherichia coli and Staphylococcus aureus (as shown in Figure 6 a, b shows the CNC1-PAA-T-Ag0.6 sample).

[0056] Embodiment 5:

[0057] As described in Example 2, except that the amount of nanocrystalline cellulose used in step (2) is 30 ml.

[0058] Example 5 The composite hydrogel obtained had a tensile strength of 0.22 MPa and an elongation at break of 196% (e.g. Figure 4 The bovine serum albumin (BSA) absorption rate was 10.8 g / g gel (as shown in a). Figure 5 The CNC3-PAA-T-Ag0.6 sample in a is shown in the test method as in Example 1). The DPPH free radical scavenging rate is 90.3% (as shown in Figure 3 a), the cell activity was 91.7% after 24 hours (MTT method). It has a significant inhibitory effect on Escherichia coli and Staphylococcus aureus (as shown in Figure 6 a, b shows the CNC3-PAA-T-Ag0.6 sample).

[0059] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.

Claims

1. A composite hydrogel, characterized in that: The preparation method thereof comprises: S1. Preparation of tannin-nanosilver composite; S2. Use tannin-nanosilver complex to stimulate free radical polymerization of acrylic acid monomers, and use nanocellulose to improve the strength to obtain nanocellulose-polyacrylic acid-tannin-nanosilver hydrogel.

2. The composite hydrogel according to claim 1, characterized in that Step S1: The tannin-nanosilver composite is prepared by the following method: The tannin and silver nitrate are mixed and reacted under light-proof conditions to obtain a tannin-nanosilver complex.

3. The composite hydrogel according to claim 2, characterized in that The mass ratio of tannin to silver nitrate is 1:(0.1-2); The reaction time is 0.5-5 hours; Reaction pH 5-7; The obtained tannin-nanosilver complex is spherical particles with a particle size of 10-30 nm.

4. The composite hydrogel according to claim 3, characterized in that The tannin is larch tannin, bayberry tannin, quebracho tannin and / or black wattle tannin.

5. The composite hydrogel according to claim 1, 2, 3 or 4, characterized in that: Step S2: The hydrogel is prepared by the following method: The tannin-nanosilver composite, nanocellulose, acrylic acid monomer and crosslinking agent are uniformly mixed, and then an initiator is added, and after being uniformly stirred, the mixture is reacted at a temperature not higher than 30° C. for 20-30 minutes to obtain a nanocellulose-polyacrylic acid-tannin-nanosilver composite hydrogel.

6. The composite hydrogel according to claim 5, characterized in that Step S2: After the materials are mixed, they are stirred for 3-5 minutes, poured into a film-forming container, and reacted at 15-30° C. for 20-30 minutes to obtain a nanocellulose-polyacrylic acid-tannin-nanosilver composite hydrogel.

7. The composite hydrogel according to claim 5, characterized in that The volume ratio of nanocellulose to tannin-nanosilver composite (1-5): 1; The mass ratio of nanocellulose to acrylic acid is 1:(1-30); The amount of initiator used is 0.05-2% of the mass of the acrylic acid monomer, and the initiator is potassium persulfate or ammonium persulfate; The amount of the cross-linking agent used is 0.5-3% of the mass of the acrylic acid monomer, and the cross-linking agent is polyethylene glycol diacrylate or N,N'-methylenebisacrylamide.

Citation Information

Patent Citations

  • Polyacrylamide-nanocellulose crystal-silver nanoparticle composite conductive anti-freezing organic hydrogel as well as preparation method and application thereof

    CN113248730A

  • Preparation method of self-healing antibacterial tissue adhesion hydrogel

    CN115715821A

  • Method to produce in SITU self-assembled multifunctional nanocomposite hydrogel and its uses thereof

    WO2022136666A1